Designing "WIBIZZ" as a Bus Rental Website to Facilitate the Booking Process and Rental Management - Zulkifli, Moh. Firdaus Fasa (International Journal of Science, Engineering, and Information Technology, 2024)
This journal discusses the design and implementation of a bus rental website with the name "WIBIZZ" which aims to increase efficiency in the bus rental ordering and management process. In the current digital era, using websites as a platform to provide bus rental services has become an attractive solution for transportation service providers. This research focuses on the design and implementation stages of a bus rental website that is user-friendly, responsive, and has adequate features to meet user needs. The methods used in this research include user needs analysis, web-based interface design, and development using the latest technology. The result of this research is a bus rental website that can be used by prospective renters easily and efficiently. The features provided include searching for bus schedules, route selection, online ticket ordering, payment management, as well as reporting and tracking rental status. It is hoped that with this website, the bus rental ordering and management process will become faster, more efficient and transparent for service providers and prospective renters. In addition, increasing efficiency in bus rental operations is expected to improve service quality and overall user experience.